Uji Resistensi Antibiotik Staphylococcus aureus Isolat Kolam Renang - Makhabbah Jamilatun (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
One of the bacteria contaminating many swimming pools in Tangerang is Staphylococcus aureus. This research is conducted to identify the resistance of Staphylococcus aureus isolates found in swimming pools in Tangerang to antibiotic. The research was started with isolation of S. aureus from swimming pools in Tangerang using a selective medium of MSA (Manitol Salt Agar), followed by gram staining, catalase test and coagulase test. Antibiotic resistance test was performed using Kirby-Bauer disk diffusion method based on the recommendation of Clinical Laboratory Standards Institute (CLSI). As many as 12 isolates of S. aureus found in swimming pools in Tangerang were tested on five types of antibiotic i.e. AMP (amphycillin) (10µg), CIP (ciprofloxacin) (5µg), TET (tetracycline) (30µg), OXA (oxacillin) (1µg), and FOS (fosfomycin) (200µg). The results of the research show Staphylococcus aureus isolates found in swimming pools in Tangerang has varying degree of resistance to antibiotic. All the tested Staphylococcus aureus isolates are sensitive to amphycillin, ciprofloxacin, tetracycline, and oxacillin. Moreover, there are 8 isolates resistant to fosfomycin and 4 isolates sensitive to fosfomycin.